2018
DOI: 10.1039/c8ra00160j
|View full text |Cite
|
Sign up to set email alerts
|

l-Menthol alleviates cigarette smoke extract induced lung injury in rats by inhibiting oxidative stress and inflammationvianuclear factor kappa B, p38 MAPK and Nrf2 signalling pathways

Abstract: L-Menthol is the main ingredient of peppermint which affects various pharmacological effects such as antiinflammation and anti-oxidative activity. In this study, we aimed to evaluate the potential effects of Lmenthol on cigarette smoke extract (CSE) induced lung injury in rats. Morphology assessment results revealed that administration with L-menthol (5, 10 or 20 mg kg À1 d À1) significantly alleviated CSEinduced lung injury. Besides, L-menthol significantly reduced the inflammatory response by suppressing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Ment has multiple important biological properties, including as anti‐inflammatory, 13,14 anesthetic, 15 antimicrobial 16–18 and gastroprotective effects 14,19 . Noteworthy, intraperitoneal Ment administrations alleviated cigarette smoke‐induced lung injury in Sprague–Dawley rats by attenuating oxidative stress and inflammation 20 …”
Section: Introductionmentioning
confidence: 99%
“…Ment has multiple important biological properties, including as anti‐inflammatory, 13,14 anesthetic, 15 antimicrobial 16–18 and gastroprotective effects 14,19 . Noteworthy, intraperitoneal Ment administrations alleviated cigarette smoke‐induced lung injury in Sprague–Dawley rats by attenuating oxidative stress and inflammation 20 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies reported menthol-induced liver and kidney protection against acute injury induced by various chemical insults (26,27). Like the work by Liu et al (25), the results of these studies showed that antioxidative and anti-inflammatory mechanisms are involved in menthol-induced protection (26,27). In addition, menthol activates transient receptor potential (TRP) melastatin 8 (TRPM8) (28), which mediates its analgesic effects (29).…”
Section: Introductionmentioning
confidence: 70%
“…Besides, menthol is an ingredient of many pharmaceutical preparations effective in the management of respiratory diseases such as sinusitis, allergic rhinitis, and bronchitis ( 24 ). A recent study illustrated that menthol alleviated cigarette smoke-induced lung injury via suppression of oxidative stress and inflammation ( 25 ). Similarly, other studies reported menthol-induced liver and kidney protection against acute injury induced by various chemical insults ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Lin et al ( 32 ) contrast with those observed by Liu et al ( 42 ), who investigated the effects of menthol (L-menthol) on cigarette smoke extract (CSE) induced lung injury in rats. The study found that following CSE injury, which is characterized by acute oxidative and inflammatory damage to the lung tissue, administration of menthol led to a marked reduction in the inflammatory response.…”
Section: Influence Of Menthol On Inflammationmentioning
confidence: 85%